¿Cuál es el final del Comentario Anónimo al Tetrabiblos de Tolomeo? - Caballero-Sánchez, José Raúl (Università Cattolica del Sacro Cuore, 2021)
The Anonymous Commentary to Ptolemy’s Tetrabiblos (Anon. in Ptol.) does not end on page 180 (πάντων τῶν κέντρων) of the Wolf’s edition (published in Basel in 1559), but on page 176, line 35 (τὰ μερικώτερα ἐσιώπησε κεφάλαια). The final lemma commented by the Anonymous is ὁ μὲν οὖν τύπος (Ptol. Tetr. IV 10, 27), which are precisely the opening words of the last paragraph of Ptolemy’s Tetrabiblos. The alleged final chapter of Anon. in Ptol., entitled Περὶ χρόνων διαιρέσεως (Wolf, pp. 176, l. 36-180, l. 13), is actually entitled Περὶ χρόνων ζωῆς (L) and has no organic connection with the last chapter of Book IV of Anon. in Ptol. (properly titled Περὶ χρόνων διαιρέσεως), but with chapter 11 of Book III (Περὶ χρόνων ζωῆς).
https://www.vitaepensiero.it/pagina/autori-2233.html
Keywords: Astrología griega; Ptolomeo, Claudio - Crítica e interpetación; Ptolemy; Anonymous Commentary to Tetrabiblos; Explicit; Hephaestio of Thebes; Isaac Argyrus; Pancharius